Rs aggarwal solutions
Our top 5% students will be awarded a special scholarship to Lido.

Factorization of Polynomials | Factorization of Polynomials Exercise 3B

Question 36

𝑥^8 − 1

Looking to do well in your science exam ?  
Learn from an expert tutor. Book a free class!

𝑥^8 − 1

We can further write it as

= (𝑥^4)^2 − 1^2

Based on the equation 𝑎^2 − 𝑏^2 = (𝑎 + 𝑏)(𝑎 − 𝑏)

We get,

= (𝑥^4 + 1)(𝑥^4 − 1)

(𝑥^4 − 1) Can also be written using the formula

= (𝑥^4 + 1)((𝑥^2)^2 − 1^2)

So we get

= (𝑥^4 + 1)(𝑥^2 + 1)(𝑥^2 − 1)

By expanding the terms using the formula

We get,

= [(𝑥^2)^2 + 1^2 + 2𝑥^2 − 2𝑥^2](𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

On further simplification

= [((𝑥^2)^2 + 1^2 + 2𝑥^2) − 2𝑥^2](𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

So we get

= [(𝑥^2 + 1) − (√2𝑥)^2] (𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

Using the formula we get,

= (𝑥^2 + 1 + √2𝑥) (𝑥^2 + 1 - √2𝑥) (𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

Set your child up for success with Lido, book a class today!

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta

Question 36

𝑥^8 − 1

Looking to do well in your science exam ? Learn from an expert tutor. Book a free class!

𝑥^8 − 1

We can further write it as

= (𝑥^4)^2 − 1^2

Based on the equation 𝑎^2 − 𝑏^2 = (𝑎 + 𝑏)(𝑎 − 𝑏)

We get,

= (𝑥^4 + 1)(𝑥^4 − 1)

(𝑥^4 − 1) Can also be written using the formula

= (𝑥^4 + 1)((𝑥^2)^2 − 1^2)

So we get

= (𝑥^4 + 1)(𝑥^2 + 1)(𝑥^2 − 1)

By expanding the terms using the formula

We get,

= [(𝑥^2)^2 + 1^2 + 2𝑥^2 − 2𝑥^2](𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

On further simplification

= [((𝑥^2)^2 + 1^2 + 2𝑥^2) − 2𝑥^2](𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

So we get

= [(𝑥^2 + 1) − (√2𝑥)^2] (𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

Using the formula we get,

= (𝑥^2 + 1 + √2𝑥) (𝑥^2 + 1 - √2𝑥) (𝑥^2 + 1)(𝑥 + 1)(𝑥 − 1)

Our top 5% students will be awarded a special scholarship to Lido.

subject-cta
Connect with us on social media!
2021 © Quality Tutorials Pvt Ltd All rights reserved
`